Non-monotonic approach to Robust H control of multi-model systems - Wen, Jiwei; Nasiri, Alireza (Professor of electrical and computer engineering); Nguang, Sing Kiong; Almakhles, Dhafer J. (Emerging methodologies and applications in modelling, identification and control., 2019)
Non-monotonic Approach to Robust H? Control of Multi-model Systems focuses on robust analysis and synthesis problems for multi-model systems based on the non-monotonic Lyapunov Functionals (LFs) approach that enlarges the stability region and improves control performance. By fully considering the diversity of switching laws, the multi-step time difference, the multi-step prediction, and the expansion of system dimension, the non-monotonic LF can be properly constructed. The focus of this book is placed on the H? state feedback control, H? filtering and H? output feedback control for multi-model systems via a non-monotonic LF approach. The book's authors provide illustrative examples to show the feasibility and efficiency of the proposed methods, along with practical examples that demonstrate the effectiveness and potential of theoretical results.